Pengaruh Temperatur Reformer Bed terhadap Performa Propane Steam Reformer Menggunakan Comsol Multiphysics 5.3Âª - Kusumastuti, Rizky; Tseng, Chung-Jen; Wijayanti, Widya; Sasmoko, Sasmoko (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
Steam reforming is a method for producing hydrogen gas as a solution for renewable energy generation. One source of hydrogen in a steam reformer is propane gas. The advantage of propane gas is the ease of transportation and storage. The production of hydrogen gas in a steam reformer is certainly influenced by supporting factors such as the temperature of the reformer. In this study, propane steam reforming was simulated in 3D with COMSOL Multiphysics 5.3Âª software with bed reformer temperatures varying from 600, 650, 700, 700, 750, 800 and 850 oC with steam to carbon (S/C) ratio 3. The results show that increasing the temperature causes the density of the reformer to decrease, which in turn results in increased gas velocity. In addition, an increase in temperature in the bed reformer increases propane conversion to 87.8% and produces about 40% hydrogen at 850 oC.